UPAYA MENINGKATKAN PRESTASI BELAJAR MELALUI MEDIA AUDIO VISUAL GERAK KELAS V SEKOLAH DASAR SANTO. PETRUS MEDAN - Pasaribu, Maria Nur Setia; Sihotang, Din Oloan (Pastoralia Jurnal Penelitian Dosen, 2024)
Through two cycles of Classroom Action Research (CAR), this study assesses the use of audio-visual materials to enhance the learning achievement of fifth-grade students at St. Elementary School. Data were collected using pretests and posttests. In the first cycle, students had an average score of 59, classified as "developing." However, following the utilization of audio-visual materials, including PowerPoint presentations and films, the average score rose to 91 in the second cycle, an increase of 32 points, and was classified as "very good." Apart from improving academic performance, the utilization of audio-visual materials also increased student engagement. These materials provide visual and auditory stimuli, aiding comprehension and fostering participation and conversation in the classroom. The utility of audio-visual multimedia opens doors for more dynamic and effective learning approaches.